PENGARUH PENGGUNAAN METODE PEMBELAJARAN PROBLEM SOLVING TERHADAP HASIL BELAJAR MATERI POKOK MENENTUKAN UNSUR FISIK PUISI “TERATAI KEPADA KI HAJAR DEWANTARA” KARYA SANUSI PANE SISWA KELAS X SMA NEGERI-1 BARUS - Fatwa Alama (Universitas Negeri Medan, 2016)
his study aimed to examine the influence applying problem solvinglearning method to the learning ountcomes the subject matter determination thephysical elements of poem “The Lily to Ki Hajar Dewantara” by Sanusi Pane atgrade class X SMA Negeri 1 Barus. This research was conducted using thedescriptive and experiment method. The study population was all eighth gradestudents of SMP Negeri 1 Barus consisting of 4 classes totaling 160 student. Thesampling technique used is random sampling technique that is 25% of the totalpopulation. So that the samples are 40 students. For signaling hypothesis upheld inthis study received or rejected, the second is how inferential statistics using theformula test